Quantitative systems pharmacology modeling of tumor heterogeneity in response to BH3‐mimetics using virtual tumors calibrated with cell viability assays - Thibaud Derippe; Sylvain Fouliard; Xavier Decleves; Donald E. Mager (Wiley, 2024)
Abstract Both primary and acquired resistance mechanisms that involve intra‐tumoral cell heterogeneity limit the use of BH3‐mimetics to trigger tumor cell apoptosis. This article proposes a new quantitative systems pharmacology (QSP)‐based methodology in which cell viability assays are used to calibrate virtual tumors (VTs) made of virtual cells whose fate is determined by simulations from an apoptosis QSP model. VTs representing SU‐DHL‐4 and KARPAS‐422 cell lines were calibrated using in vitro data involving venetoclax (anti‐BCL2), A‐1155463 (anti‐BCLXL), and/or A‐1210477 (anti‐MCL1). The calibrated VTs provide insights into the combination of several BH3‐mimetics, such as the distinction between cells eliminated by at least one of the drugs (monotherapies) from the cells eliminated by a pharmacological combination only. Calibrated VTs can also be used as initial conditions in an agent‐based model (ABM) framework, and a minimal ABM was developed to bridge in vitro SU‐DHL‐4 cell viability results to tumor growth inhibition experiments in mice.